Au fil de la guerre - Schmitz, A. (Florenville : Imprimerie Rodolphe Sauté, 1947)
Bibliotheek Camille Huysmans
Dedicator: Schmitz, A., dedicatee: Huysmans, Camille
Frans
Monografie
Keywords: poëzie; Wereldoorlog 2